Describing a "mass shooting": the role of databases in understanding burden - Marisa Booty; Jayne O'Dwyer; Daniel Webster; Alex McCourt; Cassandra Crifasi (BMC, 2019)
Abstract Background The mass shooting phenomenon has gained much attention lately as this form of gun violence appears to increase in frequency. Although many organizations collect information on mass shootings (fatal and nonfatal injuries), no federal definition of this phrase exists. The purpose of this study was to highlight the different statistics that result among databases that define and track "mass shootings." Establishing definitive guidelines for a mass shooting definition could improve research credibility when presenting evidence to policy makers. Methods We obtained data for mass shootings that occurred in 2017 from four sources: Gun Violence Archive, Mother Jones Investigation, Everytown for Gun Safety, and FBI's Supplemental Homicide Report. We also examined FBI's Active Shooter Report to compare the mass shootings datasets with active shooter situations, which have been federally defined. First, we examined the overlap among databases. Then, we applied the strictest fatal mass shooting definition to the mass shooting datasets to determine whether the differences in databases could be contributing to differences in fatalities and injuries recorded. Results Gun Violence Archive recorded the most mass shooting incidents at 346 incidents in 2017, while Mother Jones only recorded 11 cases. Only 2 events were found in all four mass shooting datasets. When the strictest definition - four or more individuals fatally shot - was applied to all datasets, the number of mass shootings in 2017 ranged from 24 (Gun Violence Archive) to 5 (Mother Jones), but incidents collected still varied. Conclusions There is much variety in statistics obtained from the different sources that have collected mass shooting information, with little overlap among databases. Researchers should advocate for a standard definition that considers both fatalities and nonfatalities to most appropriately convey the burden of mass shootings on gun violence.